2002
DOI: 10.1152/ajpendo.00544.2001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cortisol on lipolysis and regional interstitial glycerol levels in humans

Abstract: Cortisol's effects on lipid metabolism are controversial and may involve stimulation of both lipolysis and lipogenesis. This study was undertaken to define the role of physiological hypercortisolemia on systemic and regional lipolysis in humans. We investigated seven healthy young male volunteers after an overnight fast on two occasions by means of microdialysis and palmitate turnover in a placebo-controlled manner with a pancreatic pituitary clamp involving inhibition with somatostatin and substitution of gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
116
5
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(131 citation statements)
references
References 40 publications
8
116
5
2
Order By: Relevance
“…However, concomitant decreases in plasma insulin and increased plasma glucagon and cortisol confounded the possible effect or effects of IL-6 on HSL activity in type 2 diabetic patients. The reduced insulin would be expected to remove the inhibition on lipolysis [37], whereas cortisol [38,39] and glucagon [40] may increase lipolysis. Thus, it is possible that any direct stimulatory effect of IL-6 could be masked by the altered hormonal milieu induced by IL-6 infusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, concomitant decreases in plasma insulin and increased plasma glucagon and cortisol confounded the possible effect or effects of IL-6 on HSL activity in type 2 diabetic patients. The reduced insulin would be expected to remove the inhibition on lipolysis [37], whereas cortisol [38,39] and glucagon [40] may increase lipolysis. Thus, it is possible that any direct stimulatory effect of IL-6 could be masked by the altered hormonal milieu induced by IL-6 infusion.…”
Section: Discussionmentioning
confidence: 99%
“…High ambient CORT robustly increased serum NEFA levels, an expected consequence of increased adipose tissue lipolysis 58 and a probable contributor to CORT-induced insulin resistance. 59,60 Treatment with RSG modestly decreased serum NEFA but was unable to fully counteract the effect of HiCORT.…”
Section: Pparc In Rats With Hypercorticosteronemia M Berthiaume Et Almentioning
confidence: 96%
“…Acc, acetyl-CoA carboxylase; Acsl, long chain acyl-CoA synthetase; Agpat, 1-acylglycerol-3-phosphate O-acyltransferase; ATGL, adipose trigylceride lipase; Cpt1, carnitine palmitoyl transferase; DAG, diacylglycerol; Dgat; DAG O acyltransferase; DNL, de novo lipogenesis; Fas, fatty acid synthase; Gpat, glycerol-3-phosphate O-acyltransferase; HSL, hormone-sensitive lipase; LPL, lipoprotein lipase; mGpat, mitochondrial glycerol phosphate acyltransferase; PAP, phosphatidate phosphatase. measured by indirect calorimetry, was augmented by hypercortisolaemia, but this may have been secondary to increased R a of NEFAs (Djurhuus et al 2002).…”
Section: Effects Of Glucocorticoids On Fatty Acid Oxidation and Energmentioning
confidence: 97%
“…However, s.c. adipose tissue lipolysis (measured by A-V difference in the anterior abdominal wall) was reduced and LPL activity (calculated from adipose tissue blood flow and TAG extraction) was not altered (Samra et al 1998), suggesting that the s.c. adipose tissue may be excluded from the acute lipolytic effect of cortisol. However, Djurhuus et al (2002), who also measured increased systemic rates of lipolysis, found contradictory results using microdialysis techniques: s.c. adipose lipolysis was increased in both abdominal and leg adipose compartments in response to hypercortisolaemia (w900 nmol/l) during a pancreatic clamp with low-dose insulin replacement (Djurhuus et al 2002). The discrepancies between these studies are most likely explained by the higher insulin levels in the study by Samra et al (1998).…”
mentioning
confidence: 99%